2017
DOI: 10.1109/tit.2017.2700857
|View full text |Cite
|
Sign up to set email alerts
|

Principal Inertia Components and Applications

Abstract: We explore properties and applications of the Principal Inertia Components (PICs) between two discrete random variables X and Y . The PICs lie in the intersection of information and estimation theory, and provide a fine-grained decomposition of the dependence between X and Y . Moreover, the PICs describe which functions of X can or cannot be reliably inferred (in terms of MMSE) given an observation of Y . We demonstrate that the PICs play an important role in information theory, and they can be used to charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 78 publications
(148 reference statements)
0
61
0
Order By: Relevance
“…which is 0 up for t between 0 and H(X Y ), and linear with slope 1 for t in the interval from H(X Y ) to H(X). It is also shown that G(t) in general is different from this lower bound, namely even in the neighborhood of t = 0 it is typically positive, because in [20] it is shown that the derivative at t = 0 is typically positive. However, this is not the case for the privacy funnel function G (n) (t) of X n Y n , as n → ∞.…”
Section: Privacy Funnelmentioning
confidence: 97%
See 1 more Smart Citation
“…which is 0 up for t between 0 and H(X Y ), and linear with slope 1 for t in the interval from H(X Y ) to H(X). It is also shown that G(t) in general is different from this lower bound, namely even in the neighborhood of t = 0 it is typically positive, because in [20] it is shown that the derivative at t = 0 is typically positive. However, this is not the case for the privacy funnel function G (n) (t) of X n Y n , as n → ∞.…”
Section: Privacy Funnelmentioning
confidence: 97%
“…setting. Indeed, in [20] it is shown that the classical privacy funnel function is convex and obeys the piecewise linear lower bound…”
Section: Privacy Funnelmentioning
confidence: 99%
“…Relying on the so-called principal inertia components (PICs) [70], Calmon et al [71] showed that if χ 2 (U ; V ) < for some 0 < < 1, then the minimum mean-squared error (MMSE) of reconstructing any zero-mean unit-variance function of U given V is lower bounded by 1 − , i.e., no function of U can be reconstructed with small MMSE given an observation of V . Thus, χ 2 -information measures an adversary's ability to reconstruct functions of U from V under an MMSE loss.…”
Section: F -Informationmentioning
confidence: 99%
“…Our strategy is based on identifying a family of analog mappings h(·) for which z corresponds to the scenario studied in Section III-B. To that aim, we use PIC-based analysis [16], which provides a decomposition of the statistical…”
Section: Quadratic Estimation Tasksmentioning
confidence: 99%
“…Our model-aware analysis characterizes the achievable accuracy in recovering the desired information under bit constraints for tasks which can be modeled as a linear function of the measurements as in, e.g., Rayleigh fading MIMO channel estimation [13]. Then, we show how the proposed approach can be extended to more involved tasks by utilizing the mathematical tool of principal inertia compoenents (PICs) [16]. Specifically, we show that PICs can facilitate identifying a proper transformation of the measurements from which the task can be treated as approximately linear, allowing to use the proposed task-based quantizer.…”
Section: Introductionmentioning
confidence: 99%